Electrochemical doping of three-dimensional graphene networks used as efficient electrocatalysts for oxygen reduction reaction1. Issue 21 (7th June 2015) - Wang, Zhijuan; Cao, Xiehong; Ping, Jianfeng; Wang, Yixian; Lin, Tingting; Huang, Xiao; Ma, Qinglang; Wang, Fuke; He, Chaobin; Zhang, Hua
<x xml:space="preserve">Abstract</x> Three-dimensional graphene networks (3DGNs) doped with a mono-heteroatom of N or B, or dual-heteroatoms of N and B were fabricated, which exhibit excellent oxygen reduction reaction (ORR) performance.